Alterations in Cell Cycle and Induction of Apoptotic Cell Death in Breast Cancer Cells Treated with α-Mangostin Extracted from Mangosteen Pericarp - Kurose, Hitomi (Hindawi Publishing Corporation, 2012)
The development of molecularly targeted drugs has greatly advanced cancer therapy, despite these drugs being associated with some serious problems. Recently, increasing attention has been paid to the anticancer effects of natural products. α-Mangostin, a xanthone isolated from the pericarp of mangosteen fruit, has been shown to induce apoptosis in various cancer cell lines and to exhibit antitumor activity in a mouse mammary cancer model. In this study, we investigated the influence of α-mangostin on apoptosis and cell cycle in the human breast cancer cell line MDA-MB231 (carrying a p53 mutation, and HER2, ER, and PgR negative) in order to elucidate its anticancer mechanisms. In α-mangostin-treated cells, induction of mitochondria-mediated apoptosis was observed. On cell-cycle analysis, G1-phase arrest, increased p21(cip1) expression and decreases in cyclins, cdc(s), CDKs and PCNA were observed. In conclusion, α-mangostin may be useful as a therapeutic agent for breast cancer carrying a p53 mutation and having HER2- and hormone receptor-negative subtypes.